2018
DOI: 10.1111/echo.13884
|View full text |Cite
|
Sign up to set email alerts
|

Safety of nifedipine in threatened preterm labor: Investigation by three‐dimensional echocardiography

Abstract: According to RT3DTTE measurements, in pregnant women treated with nifedipine for tocolysis, there were no detrimental cardiovascular effects detected 48 hours postnifedipine treatment. RT3DTTE could show accurately the compensatory response of the left heart to the cardiovascular changes induced by treatment with nifedipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…Studies suggest that a reduction in the blood pressure may occur in normotensive pregnant women who underwent tocolysis with nifedipine, however, often without any symptoms or clinical repercussions. 21,22 There is a report on a patient using nifedipine, who developed a severe hypotension. 13 While, other studies have not shown a decrease in the blood pressure levels, 12,23,24 which may be due to a wide methodological variety and of doses used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies suggest that a reduction in the blood pressure may occur in normotensive pregnant women who underwent tocolysis with nifedipine, however, often without any symptoms or clinical repercussions. 21,22 There is a report on a patient using nifedipine, who developed a severe hypotension. 13 While, other studies have not shown a decrease in the blood pressure levels, 12,23,24 which may be due to a wide methodological variety and of doses used.…”
Section: Discussionmentioning
confidence: 99%
“…17 The effects of nifedipine described in the literature in another population, is controversial, in normotensive pregnant women. 21 Several studies have addressed the effects of nifedipine on the uteroplacental flow in pregnant women inhibiting labor with nifedipine, but the results are quite controversial. 6,12,[15][16][17]21,23,24,28 In a study carried out with 28 pregnant women who underwent tocolysis with nifedipine evaluated the blood flow of the umbilical, uterine and fetal middle cerebral arteries using velocimetric doppler parameters and the atrioventricular valves in the first 48 hours of therapy.…”
Section: Fhr (Bpm)mentioning
confidence: 99%
See 3 more Smart Citations